Ocorrência de Cryptosporidium spp. em animais exóticos de companhia no Brasil - De Souza, M. S. [UNESP]; Vieira, B. R. [UNESP]; Riva, H. G. [UNESP]; Homem, C. G. [UNESP]; Da Silva, D. C. [UNESP]; Nakamura, A. A. [UNESP]; Meireles, M. V. [UNESP] (FapUNIFESP (SciELO), 2015)
Infection by some species or genotypes of Cryptosporidium represents a potential risk to public health, mainly because of the morbidity and mortality in children from zero to five years of age and in immunocompromised patients. Although there are some reports of Cryptosporidium infection in animals raised as pets, their participation in the epidemiology of human cryptosporidiosis is uncertain and studies on this topic are still scarce. The aim of this study was to determine the occurrence, as well as to perform the molecular classification of Cryptosporidium spp. in faecal samples of exotic animals raised as pets in Brazil. A total of 386 faecal samples from six species of animals was collected and stored in a solution 5% potassium dichromate at 4°C. The oocysts were purified by centrifugal sedimentation in water-ether, followed by genomic DNA extraction and the performance of the nested-PCR to amplify a partial fragment of 18S rRNA gene. Positivity for Cryptosporidium spp. was obtained in 11.40% (44/386) of samples. The sequencing of the amplified fragments allowed the identification of Cryptosporidium tyzzeri in mice, Cryptosporidium muris in mice, hamster and chinchilla, Cryptosporidium parvum in chinchilla, Cryptosporidium hamster genotype in hamster and Cryptosporidium sp. in guinea pig. The results of this study show that there is a variety of species of Cryptosporidium present in exotic animals raised as pets in Brazil. The data suggest that these animals may have zoonotic potential and participate in the epidemiology of human cryptosporidiosis.
Occurrence of Cryptosporidium spp. in exotic animals raised as pets in Brazil
Keywords: PCR; Public health; Zoonosis